Differential impacts of contact tracing and lockdowns on outbreak size in COVID-19 model applied to China. (7th January 2022) - Browne, Cameron J.; Gulbudak, Hayriye; Macdonald, Joshua C.
Highlights: Model reactive lockdown and contact tracing quarantine measures for COVID-19. Derive final and peak outbreak size inversely proportional to quarantine rate. Model fit to China case and contact data infers efficacies of quarantine measures. Abstract: The COVID-19 pandemic has led to widespread attention given to the notions of "flattening the curve" during lockdowns, and successful contact tracing programs suppressing outbreaks. However a more nuanced picture of these interventions' effects on epidemic trajectories is necessary. By mathematical modeling each as reactive quarantine measures, dependent on current infection rates, with different mechanisms of action, we analytically derive distinct nonlinear effects of these interventions on final and peak outbreak size. We simultaneously fit the model to provincial reported case and aggregated quarantined contact data from China. Lockdowns compressed the outbreak in China inversely proportional to population quarantine rates, revealing their critical dependence on timing. Contact tracing had significantly less impact on final outbreak size, but did lead to peak size reduction. Our analysis suggests that altering the cumulative cases in a rapidly spreading outbreak requires sustained interventions that decrease the reproduction number close to one, otherwise some type of swift lockdown measure may be needed.